SOIL SOLARIZATION IN THE CONTROL OF BEAN DISEASES CAUSED BY Sclerotium rolfsii - Tomazeli, Vanessa Nataline; Santos, Idalmir dos; Morales, Rafael Gustavo Ferreira; Figueiredo, Alex Sandro Torre (REVISTA DE AGRICULTURA, 2019)
This study aimed at assessing the effects of soil solarization on diseases caused by Sclerotium rolfsii in bean plants. Treatments consisted of solarization of a soil previously infested with S. rolfsii and a standard treatment (no solarization). A randomized block experimental design was adopted, with four replications. We assessed disease severity by measuring emergence, final stand, incidence, and severity of the disease. Soil microbial activity and number of viable sclerotia were evaluated after the second crop was grown in the first year of the experiment. Soil solarization reduced the incidence and severity of stem rot caused by the fungus S. rolfsii in beans, as well as sclerotia viability. However, solarization was not effective for total control of the pathogen.